Computational fluid flow analysis of a side mirror for a passenger car - Prabagar, Murukesavan (2012)
Today, reducing the carbon dioxide emissions is vital. The car industry has a responsibility to reduce the fuel consumption and will thereby reduce carbon dioxide emissions. One of the main questions in the automotive industry is how to go about this. One possibility is to change the propulsion system. Another option is to reduce the aerodynamic drag of the car; the topic of this thesis. The drag is of great importance when it comes to velocities over 60 km/h. There are many parts of the car that contribute to drag. One such part is the side-view mirrors. The mirrors increase the total amount of drag by 2-7 percent. The mirror plays a major role in drag contribution for the entire car and therefore mirror optimization is considered very important. Mirror optimization is not an easy task due to uncertainties in the CFD simulations of a few drag counts which makes it impossible to trust all findings. In order to find a good mirror design, a combination of wind tunnel testing in full scale, and CFD simulations is necessary. Mirror design optimization shows great potential. This thesis describes the evaluation of aerodynamic flow effects of a side mirror towards a passenger car based on the side view using ANSYS Fluent CFD simulation software. The parameters that are found in this research are pressure coefficient, total pressure, drag coefficient and lift coefficient. The pressure coefficient of the side mirror designs is evaluated to analyze the unsteady forces that cause fluctuations to mirror surface and image blurring. The fluctuation also causes drag forces that increase the overall drag coefficient, resulting in higher fuel consumption and emission. There are 3 types of model tested in this research. The model is tested in simulation using the speeds of 16.67m/s (60km/h), 25m/s (90km/h) and 33.33m/s (120km/h). The models are then compared using their drag coefficient and lift coefficient. The results indicate that the halfsphere design shows the most effective design with less pressure coefficient which causes fluctuation and has low drag and lift coefficient.